Strengthening Academic Digitalization Policies to Enhance Student Service Quality at State Islamic Universities - Muh. Hambali (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The strengthening of academic digitalization policies is a process of improving student services through the utilization of digital technology. Student academic activities encompassing learning, research, and academic administration are facilitated by digital platforms to help ensure the quality of graduates. These fundamental needs can transform services for the better, provided that digital infrastructure, specifically internet networks, servers, applications, and data security, is well-established. Conversely, if these basic services fail to meet quality standards, it will result in a decline in student quality. In this context, strengthening policies to undertake digital transformation in order to fulfill student academic services is a timely and strategic breakthrough. This study aims to critically analyze the strengthening of academic digitalization amidst the era of disruption, specifically at UIN Maulana Malik Ibrahim Malang, in enhancing student quality. This study employs a qualitative approach with a case study method, where data were obtained through in-depth interviews, documentation studies, and participant observation. The primary data sources consist of institutional documents, particularly those concerning the strengthening of academic digitalization policies. The research results indicate that strengthening academic digitalization policies contributes significantly to maximizing service quality through the implementation of 'new ways of working.' This is achieved through digital innovation for academic and administrative efficiency, accountable budget allocation within the RKAKL to expand service access, and the university's mission to integrate science and Islam across all learning policies and administrative services for students. These findings confirm that leadership policy reinforcement through digital technology can address internal challenges while simultaneously enhancing the competitive quality of UIN graduates in the global arena.